A practical methodology for predicting electricity consumption of urban residential buildings - YURTSEVER, ÖZLEM (My University, 2022)
It is a challenging task for determining the emissions and energy-saving options for counties and countries. In order to overcome this issue, two new concepts are introduced in this study. These are residential base electricity consumption and residential base natural gas consumption. A new model that estimates the total energy consumption of urban residential buildings from the available electricity consumption data is developed. The model employs heating degree days (HDD) and cooling degree days (CDD) parameters to predict the energy consumption for heating and cooling purposes. A month with zero or almost zero values of both HDD and CDD is considered as \"base month.\" These months when there is neither heating nor cooling, plays a key role in this study. The proposed model is applied to a county with a population of over 62,000 located in Southern Turkey, and the total electricity consumption is calculated with 1.24% accuracy. The validity and accuracy of the model are tested by theoretical electricity calculations, coal, and wood consumption. Accordingly, while annual electrical heating is equal to 2618 kWh/year for an average house of 96 m(2), for the coal and wood burning households, the annual energy consumption values are 2190 and 2616 kWh/year, respectively.
Keywords: Tarımsal Bilimler; Çevre Mühendisliği; Kimya Mühendisliği ve Teknolojisi; Mühendislik ve Teknoloji; Agricultural Sciences; Environmental Engineering; Chemical Engineering and Technology; Engineering and Technology; MÜHENDİSLİK, ÇEVRE; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); MÜHENDİSLİK, KİMYASAL; ÇEVRE BİLİMLERİ; Çevre / Ekoloji; Tarım ve Çevre Bilimleri (AGE); ENGINEERING, ENVIRONMENTAL; ENGINEERING; Engineering, Computing & Technology (ENG); ENGINEERING, CHEMICAL; ENVIRONMENTAL SCIENCES; ENVIRONMENT/ECOLOGY; Agriculture & Environment Sciences (AGE); Atık Yönetimi ve Bertarafı; Kirlilik; Doğa ve Peyzaj Koruma; Çevre Kimyası; Çevre Bilimi (çeşitli); Genel Mühendislik; Mühendislik (çeşitli); Akışkan Akışı ve Transfer İşlemleri; Kolloid ve Yüzey Kimyası; Kimyasal Sağlık ve Güvenlik; Kataliz; Kimya Mühendisliği (çeşitli); Genel Kimya Mühendisliği; Su Bilimi; Fizik Bilimleri; Yaşam Bilimleri; Waste Management and Disposal; Pollution; Nature and Landscape Conservation; Environmental Chemistry; Environmental Science (miscellaneous); General Engineering; Engineering (miscellaneous); Fluid Flow and Transfer Processes; Colloid and Surface Chemistry; Chemical Health and Safety; Catalysis; Chemical Engineering (miscellaneous); General Chemical Engineering; Aquatic Science; Physical Sciences; Life Sciences; energy efficiency; greenhouse gas; sustainability; GREENHOUSE-GAS EMISSIONS; ENERGY-CONSUMPTION; CLIMATE-CHANGE; GHG EMISSIONS; DEMAND; SECTOR; TRANSPORTATION; FOOTPRINT; CITIES; energy efficiency; greenhouse gas; sustainability